Technology Acceptance Model on SIMBA Adoption in SIM-ZAWA Subject - Rafikasari, Elok Fitriani; Handayani, Fitri; Supriyadi, Ahmad; Rasmuin, Rasmuin (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
SIMBA is one of the technologies in zakat management information systems developed and used by BAZNAS. This system produces an accountable and transparent zakat report because it is integrated from the central to regional BAZNAS. The use of SIMBA in the SIM-ZAWA course has not been maximally applied for various reasons, so an analysis of lecturers and students' perceptions in using SIMBA is needed. The most appropriate technology acceptance model is the Technology Acceptance Model (TAM) which is then analyzed using Bayesian Structural Equation Modeling (SEM) because of its tiered structure and the assumptions that are not fulfilled in SEM analysis. This research was conducted on 50 respondents are students who are currently and have taken SIM-ZAWA courses. The results showed that the acceptance of SIMBA technology was influenced by Perceived Ease of Use (PE) and Perceived Usefulness (PU) with PU and PE influenced by Subjective Norm (SN) and Innovativeness (I).